Finding allies and making revolution : the early years of the Chinese Communist Party - Saich, Tony (Brill, 2020)
"What does a Dutchman have to do with the rise of the Chinese Communist Party? Finding Allies and Making Revolution by Tony Saich reveals how Henk Sneevliet (alias Maring), arriving as Lenin's choice for China work, provided the communists with two of their most enduring legacies: the idea of a Leninist party and the tactic of the united front. Sneevliet strived to instill discipline and structure for the left-leaning intellectuals searching for a solution to China's humiliation. He was not an easy man and clashed with the Chinese comrades and his masters in Moscow. This new analysis is based on Sneevliet's diaries and reports, together with contemporary materials from key Chinese figures, and important documents held in the Comintern's China archive"--